Various Reporting Narratives That Represent Women With Arms In Various Online Media - Rinrin Rianti; Agus Hamdani (Journal on Education, 2023)
As a country that has the largest number of Muslims in the world, Indonesia is a country that is vulnerable to the issue of terrorism. This study aimed to examine news on the link between terrorism and news developing in online media regarding a woman who pointed a gun at Presidential Guard at the State Palace. The data for this study were sourced speech and dialogue in the online media Tvonenews.com, Nasional.kompas.com, and CNBCINdonesia.com about women carrying firearms to the State Palace. Data collection methods and techniques used the content analysis method with the critical discourse analysis approach of the Teun A Van Dijk model. The results of the study showed that women carrying pistols were narrated by the online media Tvonenews.com with the headline "Voice Veil Breaks Through the Presidential Palace, PKS Politicians: Don't Enter MENTAL DISORDERS" and Nasional.Kompas.com with the headline "Moeldoko: Women Pointing Gun at Presidential Guard Allegedly Having Individual Motives" has attempted to link the case to Islamic religious identity, in other words, terrorism. However, the online media, CNBCIndonesia.com entitled “A Woman is Pointing a Gun at Paspampre, These are the Facts…” does not make any connection between this and terrorism or Islamic faith.